Adsorventes alternativos a partir de gelatina recuperada de resíduos de couro e nanotubos de carbono para remoção de contaminantes emergentes - Rigueto, Cesar Vinicius Toniciolli (2021)
Industries of the transformation of animal hides into leather are responsible for the generation of solid waste in collagen. Gelatin is a biopolymer that can be obtained from collagen hydrolysis and has been promising in studies involving the production of adsorbents. Carbon nanotubes (CNT’s) are used as reinforcements for polymeric matrices, since the use of pure CNT’s powder as an adsorbent causes the blocking of industrial filters, and the separation process is difficult. Thus, this work aimed to develop composite beads from gelatin recovered from chromium-tanned leather wastes (RCTLW) and CNT’s. For comparison purposes, standard beads were produced, containing only commercial gelatin or RCCC gelatin. The drip emulsification method was used in the preparation of the beads, with a concentration of 8% (w/w) of commercial and RCTLW (w/v) gelatins, respectively, and additions of 0 and 5% (w/w) of CNT’s in relation to the gelatin weight. The adsorbents were characterized by Scanning Electron Microscopy (SEM), Fourier Transform Infrared Spectroscopy (FTIR), Thermovogravimetry (TGA), Point of zero charge (pHPZC). Composite beads (CNT’s and gelatin) were further characterized by X-Ray Diffraction (XRD), and the Swelling and Water retention capacities were also determined. The batch adsorption tests (equilibrium, kinetic, and desorption, and reuse) were conducted using the tartrazine yellow dye and diclofenac sodium as experimental models. In the characterization of the adsorbent beads, it was found smooth surface, diameter around 1.0 mm, pHPZC of 5.0 and 5.5 for the composite beads, and without the addition of CNT’s, respectively. The FTIR analysis indicates similar structures between the two types of gelatin (commercial and RCTLW). The addition of CNT’s to composites was proven from the XRD analysis. In thermogravimetry, two weight loss events at 225 ºC and 325 ºC were observed, related to water evaporation and depolymerization of gelatin protein, respectively. The adsorption capacities of the tartrazine varied from 131.32 to 263.13 mg.g-1, while for diclofenac the variations were from 17.51 to 36.35 mg.g-1. In mathematical modeling, the Langmuir, Freundlich, and Redlich-Peterson models coefficients of determination (R²>0.90), being efficient to describe the adsorption of tartrazine and diclofenac by the adsorbent beads. The classifications of the profiles of the isothermal curves were changed according to the material used, suggesting changes in the mechanism. Electrostatic interactions and hydrogen bonds possibly were the mechanisms involved in the adsorption of the tartrazine and diclofenac, respectively. In kinetics, for both materials, the adsorption density of the dye continued to increase after 300 min, while for diclofenac, after 80 min the adsorption rate became constant. In regeneration, both beads were used for up to 10 cycles, with an adsorption resource of around 100 mg.g-1. In general, the addition of CNT’s did not increase the adsorption capacities of commercial gelatins and RCTLW, and gelatin as a single material showed a promising adsorbent. Also, the RCTLW showed adsorption capacities similar to commercial gelatin, therefore, the present work can contribute as a basis for further studies in the field of materials science and adsorption.